ANALISIS KUALITAS CRUDE PALM OIL (CPO) BERDASARKAN PARAMETER FREE FATTY ACID (FFA), MOISTURE DAN DIRT - Arum Lailan Safitri; Miftahul Husnah (Universitas Islam Sumatera Utara, 2025)
Indonesia is one of the largest producers of Crude Palm Oil (CPO) in the world; therefore, CPO quality control is important to maintain product quality according to standards. This study aims to analyze the quality of CPO based on Free Fatty Acid (FFA), moisture, and dirt parameters and to evaluate its conformity with the SNI 01-2901-2006 standard. The study used a quantitative method with an experimental approach through laboratory testing of CPO samples from Tank 2 and Tank 4 for six days of observation. The testing was carried out using titration, oven-based heating, and filtration methods related to physicochemical analysis and material separation. The results showed that the FFA values ranged from 2.62%–3.08%, moisture from 0.13%–0.17%, and dirt from 0.024%–0.032%. All test results were still below the maximum limit of the SNI 01-2901-2006 standard, indicating that the produced CPO quality was still classified as good and met the established quality standards.